2021
DOI: 10.15586/ijfs.v33isp1.2027
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of essential oils in Iranian traditional animal oil: an assessment of physicochemical and sensory assessment

Abstract: This study aimed to incorporate the herbal essential oils (Ziziphora tenuior L. (Z. tenuior), Ferulago angulata (F. angulata), and Bunium persicum (B. persicum)) all in three levels (5, 7, and 10% w/w) and tertiary butyl hydroquinone (100, 200, and 300 ppm) to evaluate the oxidation stability of Iranian animal oil (IAO). Z. tenuior, F. angulata, and B. persicum (5, 7, and 10% w/w) and tertiary butyl hydroquinone (100, 200, and 300 ppm) were added to IAO. The physicochemical properties and color analysis, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Numerous studies demonstrated that plant extracts and essential oils (EOs) have been used worldwide as food preservatives since they are the richest sources of phytochemicals (Azizi et al ., 2021). Phenolic compounds are among the leading groups amongst the phytochemicals that have antioxidant and antimicrobial performance (Jafarzadeh et al ., 2020).…”
Section: The Roles Of Plant‐based Formulations As Food Additivesmentioning
confidence: 99%
“…Numerous studies demonstrated that plant extracts and essential oils (EOs) have been used worldwide as food preservatives since they are the richest sources of phytochemicals (Azizi et al ., 2021). Phenolic compounds are among the leading groups amongst the phytochemicals that have antioxidant and antimicrobial performance (Jafarzadeh et al ., 2020).…”
Section: The Roles Of Plant‐based Formulations As Food Additivesmentioning
confidence: 99%
“…The mechanisms of oxidative reactions and the action of antioxidant compounds at temperatures above 100°C differ from those at temperatures below 100°C (Amiri et al., 2021 ; Azizi et al., 2021 ; Choudhary et al., 2023 ; Gao et al., 2023 ; Mohamadi et al., 2023 ; Tayebeh et al., 2021 ). For example, increasing the content of tocopherol and polyphenolic compounds in edible oils is possible during thermal processing at 180°C for 20 h compared to their initial values (AlGhamdi et al., 2023 ; Veronezi & Jorge, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Natural ingredients such as essential oils and plant extracts have great potential for increasing the barrier properties, mechanical strength of packaging films, and shelf life of different food products. These extracts have diverse biological functions, including antioxidant and antimicrobial, and are generally considered safe ( [11][12][13] ; Shah and Mir, 2022) ). Starch-based films have greatly added different active substances from natural sources.…”
Section: Introductionmentioning
confidence: 99%